Real-world effect of intermittent calorie-restricted diet on type 2 diabetes remission: a dual-cohort retrospective study - Xiao, Zhiyong; Yin, Xinhong; Lai, Xihu; Zhou, Xu; Zhang, Yewu; Yang, Dongliang; Wu, Ruiyu; Wang, Huiqing; Zhou, Jiali; Yang, Xiao; Zhou, Bin; Luo, Wu; et al. (Frontiers in Nutrition, 2025)
AimsRandomized controlled trials (RCTs) have demonstrated that intermittent calorie-restricted diet (ICR) can lead to diabetes remission. We aimed to assess the diabetes remission with ICR among patients with type 2 diabetes (T2D) in real-world settings.Materials and methodsWe performed a retrospective, dual-cohort study (January 2022–July 2023) using real-world data from Chinese patients with T2D. The ICR cohort consisted of 1,069 patients following an intermittent calorie-restricted diet, while the control cohort consisted of 1,099 patients receiving Dietary Guidelines for Diabetes in China (2017 Edition). The primary outcome was diabetes remission. Secondary outcomes included reductions in antidiabetic medication use and changes in fasting blood glucose (FBG). Subgroup evaluations for the sensitivity analysis were conducted to further assess outcomes. The study employed a combination of univariate and multivariate analyses, including Linear Mixed-Effects Models (LMM), Generalized Linear Mixed-Effects Models (GLMM), and Cox regression with propensity score-weighted Inverse Probability Weighting (IPW), to evaluate relationships between cohort and outcomes.ResultsIn real-world settings, the ICR cohort achieved significantly higher remission rates (20% vs. 2%, p < 0.001), greater medication reduction (61% vs. 22%, p < 0.001). After IPW adjustment, ICR remained superior for remission (OR: 11.02, 95% CI: 8.12–14.96) and reduce medication usage (Estimate: 6.26, 95% CI: 5.61–6.99, p < 0.001). Subgroup analyses confirmed consistent benefits across FBG levels and diabetes durations.ConclusionThis study demonstrated the practical efficacy of ICR in achieving diabetes remission. These findings establish dietary interventions as a powerful and viable strategy for T2D remission.